STROKE NON HEMORAGIK DENGAN FIBROMA VENTRIKEL KIRI - William, Yosef; Putra Gunadhi, I Gusti Ngurah (journal of internal medicine, 2010)
Cardiac ! broma is a rare case. It?s incidents about 3.2% from all incident of cardiac and pericardia tumor, that most oftenfound in infancy and adolescence, and less frequently in adults. Cardiac ! broma is a benign solitary tumor of the heart which isconsist of ! brous tissue that most commonly in the left ventricle or the interventricular septum. This case was a male 51 yearsold with chief complaint of decrease of consciousness about 3 days prior admitted to hospital. He was consulted from neurologistwith stroke non hemorrhagic. He was used to be a smoker since young adult. At ! rst time, we found weakness both of extremity,and cardiomegaly without abnormality in heart?s sound. ECG shown inferior old myocardial infarction. The head CT Scan shownthere was a infarct in capsulla interna of left sub cortex hemisphere. And from echocardiography, we found there?s a mass onleft ventricular with its size was 2 x 2.5 cm. We diagnosed with observation of left ventricular mass caused by probable cardiacmyxoma, coronary arterial disease/OMI inferior/FC II, and stroke non hemorrhagic. After two months he had stroke, patient hada total resection of his cardiac tumor. It was done with open heart technique. From histologic ! ndings, we found a white solidmass in macroscopic, and in microscopic, there was ! brous tissue with focal calci! cation at the edge of tissue, which surroundednecrosis coagulated area. One week after surgery, he was went home in well condition and had some medications, i.e. vitamin Bcomplex, acetosal 100 mg od , and captopril 6.25 mg tid. A cardiac ! broma was a rare cardiac tumour. Until now, pathogenesisof cardiac ! broma still unknown. Diagnostic of cardiac ! broma can get from echocardiography and histologic examination.Treatment of cardiac ! broma are symptomatic for its complication, and invasive procedure, i.e. total or subtotal resection, andcardiac transplantation